Reading comprehension intervention for students with autism spectrum disorder level 1 using the iPad graphic organizer app - Alzahrani , Asma N (Journal of Education and e-Learning Research, 2023)
Research has found that students with autism spectrum disorder (ASD) may face difficulties in reading comprehension. This study explored the functional relationship between the use of a graphic organizer (GO) app on the iPad and the number of correct independent responses to reading comprehension questions by one student with ASD Level 1. The study used an applied behavior analysis intervention that used an ABAB design. Aseven-question reading comprehension questionnaire was used to collect data Strong evidence was found of a functional relationship between the use of the graphic organizer (GO) on the iPad and an increase in correct independent responses by the student. Future research can develop to replicate the results and further explore how the use of a GO app on the iPad affects reading comprehension in students with ASD.